Transformative-Critical Education Paradigm: Investigating the Influence of Paulo Freire and Moeslim Abdurrahman in Ikatan Pelajar Muhammadiyah (1998-2008) - Khoirudin, Azaki (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2017)
This study investigated the influence of Paulo Freireâs criticaleducation and Moeslim Abdurrahmanâs Transformative Islam in IkatanPelajar Muhammadiyah (IPM). The problem statement was formulated:to what extent Freire and Moeslim influence the educational thoughtand practice of education in IPM? By using discourse analysis, thisstudy revealed that the discourse and practice of critical-transformativeeducation has evolved in IPM since the reform era in 1998-2008.The Discourse of critical education and Transformative Islam areintertwined into âManifesto of Transformative Critical Movementâincorporated in the educational guideline of IPM members. Thistransformative-critical discourse has encouraged IPM becoming apopulist student organization. Afterward, the discourse and practice ofthis organizationâs movements is accentuated by the criticism towardsinjustice and the struggle towards social transformation